Motivasi Kerja Pustakawan Inpassing Perspektif McClelland (Kajian Analisa Implementasi Permenpan Nomor 26 Tahun 2016 di Perpustakaan UIN Sunan Ampel Surabaya) - Hary Supriyatno (Media Pustakawan, 2022)
Regulations for the appointment of librarian functional positions through the inpassing channel provide opportunities for employees in the library to further improve their careers. The minimum requirement of a two-year service period to participate in the inpassing program makes the opportunity to switch to a functional. Inpassing opportunity will not only serve as a means of increasing income and make work longer, but it will also improve performance and more achievement. With competence and motivation so that all of this can be realized. This research was conducted to determine the level of work motivation of the inpassing librarian at the UIN Sunan Ampel Surabaya Library. The method used is Mixed Methods Research, which is a combination of qualitative and quantitative methods in one study to obtain more complete, valid, and objective data. Data were collected through observation, questionnaire, and interview techniques based on McClelland's three main elements of motivation, that is Achievement, Power, and Affiliation. Based on the result of quantitative data analysis, can be concluded that the level of work motivation of inpassing librarians has a high category or in the range of 96%. This result is suitable with qualitative data states that the high motivation of inpassing librarians is cause oral and written achievements, ability in managing and controlling of work section, and good interaction with managers and colleagues.